The Effect of Accounts Receivable Turnover and Inventory Turnover on Return on Assets at PT Multi Indocitra, Tbk. - Muhammad Amir; Robertilde Diani Serin; Megawhati Artinyany; A. Tendean (Pustaka Digital Indonesia, 2026)
Robertilde Diani Serin, 2024. Effect Of Accounts Receivable Turnover and Inventory On Return On Assets (ROA) at PT. Multi Indocitra, Tbk. Supervised by Andi Asad Rijal Nur and Muhamad Amir. The purpose of this study was to determine receivable turnover and inventory turnover on return on asset at PT. Multi Indocitra, Tbk 2019-2023. In this study, quantitative and qualitative data were combined. information from secondary sources. The t test, f test, correlation coefficient, coefficient of determination, descriptive quantitative, and multiple linear regression were the analytical techniques employed. Multiple linear regression Y is clearly = a + b1 X1 + b2 X2, the coefficient of determination (r^2) = 0,837 and the correlation coefficient (r) =0,914 then, the results of the t-test b1 tcount <t bable and b2 tcount < ttable and through the f test obtained the value of Fcount <ftabl this the results of the f-count test conclude that simultaneously receivables turnover and inventory turnover have a not significant effect on return on asset. The results of the t-test of receivables turnover that partially receivables turnover has a positive but insignificant impact on return on assets. Inventory Turnover that partially inventory turnover has a positive and insignificant effect on return on assets at PT. Multi Indocitra, Tbk.